2020
DOI: 10.1111/and.13657
|View full text |Cite
|
Sign up to set email alerts
|

Maternal CBZ exposure impairs testicular development, spermatogenesis and sperm parameters in male offspring at puberty

Abstract: Carbamazepine (CBZ) is widely used in the control of convulsive crisis, treatment of trigeminal neuralgia and affective disorders. This drug has been administered to pregnant women to prevent seizures, and this antiepileptic drug (AED) treatment cannot be discontinued because of the risk of seizures during pregnancy, which can be harmful to both mother and child (Pennell, 2013). CBZ crosses the placental barrier, reaching the embryo/foetus. The use of CBZ during gestation is associated with a twofold or threef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…In a preceding study, performed by our group, pregnant rats received a CBZ dose of 20 mg/kg, by intra‐peritoneal route, during two different periods of the pregnancy: (a) from 12 to 20 gestational day (GD) that consists in the initial period of the male gonad differentiation and formation of the seminiferous cords (McGivern et al., 1992), and (b) from 15 to 20 GD, corresponding to the start of the testosterone production (Habert et al., 2001). Interestingly, we observed on that occasion that there was an increase in sperm quantitative parameters in rats submitted to CBZ treatment during the intra‐uterine phase, suggesting that SC could be involved in this alteration (Oliva et al., 2020).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a preceding study, performed by our group, pregnant rats received a CBZ dose of 20 mg/kg, by intra‐peritoneal route, during two different periods of the pregnancy: (a) from 12 to 20 gestational day (GD) that consists in the initial period of the male gonad differentiation and formation of the seminiferous cords (McGivern et al., 1992), and (b) from 15 to 20 GD, corresponding to the start of the testosterone production (Habert et al., 2001). Interestingly, we observed on that occasion that there was an increase in sperm quantitative parameters in rats submitted to CBZ treatment during the intra‐uterine phase, suggesting that SC could be involved in this alteration (Oliva et al., 2020).…”
Section: Discussionmentioning
confidence: 92%
“…In a previous study, we observed an increase in sperm daily production and sperm concentration in the epididymis of offspring from rat dams that were CBZ‐treated during pregnancy (Oliva et al., 2020). These findings led us to ask whether, in this case, a possible dysregulation in Sertoli cell development and function could result in alterations of spermatogenesis.…”
Section: Introductionmentioning
confidence: 84%